Influence of the functional class of Paralympic cross-country sit-skiers on the effectiveness of competitive activity (on the example of the sprint distance) - Maksym Mishyn; Liudmyla Pavlenko; Miroslawa Cieslicka; Oleg Kamaiev; Larysa Taran (Kharkiv State Academy of Physical Culture, 2022)
Purpose: to determine the value of the functional classification and its influence on the result of the competitive activity of Paralympic cross-country sit-skiers. Material and methods: to solve the problems of the study, the data of 164 Paralympic cross-country sit-skiers were analyzed, including 98 men and 66 women, participants of the Winter Paralympic Games, namely: Sochi 2014 - 47 athletes (24 men and 25 women) PyeongChang 2018 - 61 men and 25 women), Beijing 2022 - 56 athletes (38 men and 18 women) with a functional class LW10-12 and are representatives of the sitting category, performing in the sprint ski race. During the study, the following methods were used: theoretical analysis of scientific and methodological literature and Internet sources, generalization of best practices, analysis of protocols and videos of competitive activity, methods of mathematical statistics. Results: changes were revealed in relation to representatives of different classes in the final round of the sprint ski race among athletes of the sitting category: Sochi 2014: men - LW10 - 1 and LW12 - 5, women - LW11 - 2 and LW12 - 4; PyeongChang 2018: men - LW11.5 - 1 and LW12 - 5, women - LW11 - 1 and LW12 - 5; Beijing 2022: men LW10 - 2, LW11.5 - 1 and LW12, women - LW10 - 1, LW10.5 - 1, LW11.5 - 1 and LW12 - 3. Conclusions: it has been proven that one of the topical issues in holding competitions among athletes with disabilities is the classification process aimed at fair competition between athletes, despite their individual functional capabilities; despite this, modern research proves that there are some factors that affect the result of competitive activity, but which are not taken into account by the classification system; the modern classification strategy is aimed at improving this process (percentage system), which helps to increase the competitiveness of representatives of all classes included in the sitting category.